Junctophilin‐4 facilitates inflammatory signalling at plasma membrane‐endoplasmic reticulum junctions in sensory neurons. (3rd March 2021) - Hogea, Alexandra; Shah, Shihab; Jones, Frederick; Carver, Chase M.; Hao, Han; Liang, Ce; Huang, Dongyang; Du, Xiaona; Gamper, Nikita
Abstract : Key points: Rat somatosensory neurons express a junctional protein, junctophilin‐4 (JPH4) JPH4 is necessary for the formation of store operated Ca 2+ entry (SOCE) complex at the junctions between plasma membrane and endoplasmic reticulum in these neurons. Knockdown of JPH4 impairs endoplasmic reticulum Ca 2+ store refill and junctional Ca 2+ signalling in sensory neurons. In vivo knockdown of JPH4 in the dorsal root ganglion (DRG) sensory neurons significantly attenuated experimentally induced inflammatory pain in rats. Junctional nanodomain Ca 2+ signalling maintained by JPH4 is an important contributor to the inflammatory pain mechanisms. Abstract: Junctions of endoplasmic reticulum and plasma membrane (ER‐PM junctions) form signalling nanodomains in eukaryotic cells. ER‐PM junctions are present in peripheral sensory neurons and are important for the fidelity of G protein coupled receptor (GPCR) signalling. Yet little is known about the assembly, maintenance and physiological role of these junctions in somatosensory transduction. Using fluorescence imaging, proximity ligation, super‐resolution microscopy, in vitro and in vivo gene knockdown we demonstrate that a member of the junctophilin protein family, junctophilin‐4 (JPH4), is necessary for the formation of store operated Ca 2+ entry (SOCE) complex at the ER‐PM junctions in rat somatosensory neurons. Thus we show that JPH4 localises to the ER‐PM junctional areas and co‐clusters with SOCE proteins STIM1 and Orai1 upon ER Ca 2+ store depletion. Knockdown of JPH4 impairs SOCE and ER Ca 2+ store refill in sensory neurons. Furthermore, we demonstrate a key role of the JPH4 and junctional nanodomain Ca 2+ signalling in the pain‐like response induced by the inflammatory mediator bradykinin. Indeed, an in vivo knockdown of JPH4 in the dorsal root ganglion (DRG) sensory neurons significantly shortened the duration of nocifensive behaviour induced by hindpaw injection of bradykinin in rats. Since the ER supplies Ca 2+ for the excitatory action of multiple inflammatory mediators, we suggest that junctional nanodomain Ca 2+ signalling maintained by JPH4 is an important contributor to the inflammatory pain mechanisms. Key points: Rat somatosensory neurons express a junctional protein, junctophilin‐4 (JPH4) JPH4 is necessary for the formation of store operated Ca 2+ entry (SOCE) complex at the junctions between plasma membrane and endoplasmic reticulum in these neurons. Knockdown of JPH4 impairs endoplasmic reticulum Ca 2+ store refill and junctional Ca 2+ signalling in sensory neurons. In vivo knockdown of JPH4 in the dorsal root ganglion (DRG) sensory neurons significantly attenuated experimentally induced inflammatory pain in rats. Junctional nanodomain Ca 2+ signalling maintained by JPH4 is an important contributor to the inflammatory pain mechanisms.